<h3>
Answer: 2x^2 + 6x - 4</h3>
=================================
Work Shown:
f(x) - g(x) = [ f(x) ] - [ g(x) ]
f(x) - g(x) = ( 3x^2+x-3) - ( x^2-5x+1 )
f(x) - g(x) = 3x^2+x-3 - x^2+5x-1
f(x) - g(x) = (3x^2-x^2) + (x+5x) + (-3-1)
f(x) - g(x) = 2x^2 + 6x - 4
Answer:
-8-3
Step-by-step explanation:
-4(8r+3)
-32r-12
divide both sides by 4
-8-3
Answer:
3
Step-by-step explanation:
because 3 is the only number that goes into both 3 and 27
It depends if the negative number is bigger than the positive number your answer will be a negative number/answer for example -9 - 4 your answer would be -5 since the negative number is bigger it will be the other way around for a positive number if the positive number is bigger than the negative number your answer will be positive for example 5 - -2 = 3 or positive 3.
Answer:
24 students.
Step-by-step explanation:
25% is 1/4 of 100.
6*4= The number of students.